Tissue engineering: the science, the technology and the industry - Nerem, Robert (Henry Stewart Talks, 2007)
Historical perspective, Biomedical devices and diagnostics industry, Medical implant industry, Approved tissue products, Dermagraft, Tissue engineered skin substitutes, Cell source, Matrix, Immune tolerance, Off-the-shelf availability, Embryonic stem cells, Scaffolds, Bioreactor technology, Integration into the living system, Therapeutic products, Key industry trends, Advances envisioned